MANAGING THE MONUMENT: COWS AND CONSERVATION IN GRAND STAIRCASE-ESCALANTE NATIONAL MONUMENT (Utah Environmental Law Review; Vol 29 No 2 (2009), 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} In 1996, President Clinton short-circuited decades-long negotiations over the use of contested western lands and stunned Utah’s political leaders when he designated close to 2 million acres in their state as the Grand Staircase-Escalante National Monument (GSENM). Clinton’s proclamation charged the Bureau of Land Management (BLM), for the first time in its history, with responsibility for managing a national monument, and required the agency to manage the vast lands to balance conflicting multiple uses, including cattle grazing. Various statutes mandate that federal lands that have been determined to be chiefly valuable for grazing be actively grazed. However, anti-grazing activists saw in Clinton’s action an opening to reduce or eliminate grazing on allotments contained within the newly designated national monument and found sympathy among the Monument’s new managers. The question for conservation advocates and Monument managers was, in the absence of statutory change, could the administrative process be used to reduce or eliminate grazing in the Monument? This Article examines the twists and turns in the management, administrative, and legal processes that led an anti-grazing conservation group to become the largest rancher on the Colorado Plateau.